Reflections on activity theory - Bakhurst, David (Educational review (Birmingham), 2009)
It is sometimes suggested that activity theory represents the most important legacy of Soviet philosophy and psychology. But what exactly is activity theory? The canonical account in the West is given by Engeström, who identifies three stages in the theory's development: from Vygotsky's insights, through Leontiev's articulation of the fundamental structure of activity, to a still-emerging third generation incorporating difference, discourse and dialogue into the framework. This paper argues that the resulting position is in fact in tension with the concerns of the Russian founders of the tradition. While the latter saw the concept of activity as a fundamental category to address profound philosophical questions about the possibility of mind, activity theory in the West has principally become an empirical method for modeling activity systems. The paper explores the strengths and weaknesses of views on both sides of the contrast and examines its consequences for the future of the activity-theoretical tradition.